2012
DOI: 10.1042/bj20120408
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive binding of three antagonistic peptides to the ephrin-binding pocket of the EphA4 receptor

Abstract: SYNOPSIS The EphA4 receptor tyrosine kinase interacts with ephrin ligands to regulate many processes, ranging from axon guidance and nerve regeneration to cancer malignancy. Thus, antagonists that inhibit ephrin binding to EphA4 could be useful for a variety of research and therapeutic applications. Here we characterize the binding features of three antagonistic peptides (KYL, APY and VTM) that selectively target EphA4 among the Eph receptors. Isothermal titration calorimetry analysis demonstrates that all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 57 publications
3
62
1
Order By: Relevance
“…A KYL peptide has been shown to specifically inhibit EphA4 activation 41 . Treatment of cocultures with the KYL peptide, but not the KYL-P7A control peptide 41 , blocked 90% of EphA4 phosphorylation in the HMLER90hi cells and significantly reduced the secretion of the three cytokines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A KYL peptide has been shown to specifically inhibit EphA4 activation 41 . Treatment of cocultures with the KYL peptide, but not the KYL-P7A control peptide 41 , blocked 90% of EphA4 phosphorylation in the HMLER90hi cells and significantly reduced the secretion of the three cytokines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present study shows that Rhy and KYL peptide (40), which binds to the ligandbinding domain of EphA4, effectively alleviated Aβ-induced synaptic dysfunction and synaptic plasticity defects in AD transgenic mouse models. This suggests that blockade of EphA4 activity can be potentially developed as a therapeutic strategy for the treatment of AD.…”
Section: Discussionmentioning
confidence: 93%
“…Other than multi-target RTK inhibitor, Noberini et al in Pasquale EB's lab identified two isomeric 2, 5-dimethylpyrrolyl benzoic acid derivatives able to selectively inhibit ephrin binding to EphA4 and EphA2 as well as the function of these receptors in live cells [43]. In fact, this lab has discovered a series of small molecules targeting Eph receptors [44][45][46], which may serve as lead compounds for drug development, as well as targeting agents to deliver drugs or imaging agents to tumors. The antibody-based drugs targeting EphA2 have also been developed, including an antibody-drug conjugate (MEDI-547) composed of a fully human monoclonal antibody against both human and murine EphA2 (1C1) and the tubulin polymerization inhibitor monomethylauristatin F [47] and EA5 [48].…”
Section: Potential Therapeutic Reagents Targeting Ephs/ Ephrins In Lumentioning
confidence: 95%